A NEW SPECIES OF Bolivar Zaldívar-Riverón et Rodríguez-Jiménez (BRACONIDAE, DORYCTINAE) FROM BRAZIL, WITH NEW RECORDS OF THE AMAZONIAN B. ecuadorensis Zaldívar-Riverón et López-Estrada - Nunes, Juliano Fiorelini; Penteado-Dias, Angelica Maria; Souza-Gadelha, Sian De; Zaldívar-Riverón, Alejandro (Zootaxa, 2016)
A new species of the doryctine genus Bolivar (Braconidae), B. brasiliensis sp. nov., is described from the Atlantic coastal region in Brazil. New records and taxonomic notes of the Amazonian B. ecuadorensis Zaldívar-Riverón et López-Estrada are also provided.